Bioinformatics analysis of cis-regulatory elements in Mbl1 and Mbl2 genes in Rattus norvegicus - Bondarenko, V.S.; Obolenska, M.Yu. (2015)
Aim. To identify and characterize with the help of bioinformatics the transcription factors binding sites in promoters of Mbl1 and Mbl2 genes, encoding mannose binding lectins in Rattus norvegicus. Methods. Bioinformatics, MatInspector software. The position weight matrices of transcription factor binding sites were obtained from the Matrix Family Library Version 9.0. Within the frame of the program we selected the binding sites, the cognate transcription factors of which are specifically expressed in the liver and immune cells, and have passed the filter for conservation after comparison with the binding sites in orthologous genes in Mus musculus. Results. The promoters of both genes share the binding sites for the members of the four common families of transcription factors (HNF, homeodomain transcription factors, GRs and ETS factors). The promoters of Mbl1 and Mbl2 gene possess correspondingly additional binding sites for the members of six (AP1 related factors, Ccaat/Enhancer Binding Proteins, FOX, p53, NFAT, ISGF3) and four (cAMP-responsive element binding proteins, heat shock factors, Nf-?B/c-rel and TATA binding protein) families of transcription factors. The Mbl1 specific transcription factors are mainly involved in the regulation of differentiation, development, metabolic homeostasis, organogenesis and cell cycle. Unlike them the Mbl2 specific transcription factors are more prone to mediate a stress-response. Conclusion. The variety of transcription factors potentially involved in regulation of the Mbl1 and Mbl2 transcription argue for these genes involvement in various cellular processes with specific role of each gene. The obtained results provide the basis for the task-oriented wet-lab bench experiments on their regulation.